Demonstrating full-scale post-combustion CO2 capture for coal-fired power plants through dynamic modelling and simulation - Lawal, Adekola; Wang, Meihong; Stephenson, Peter; Obi, Okwose (Elsevier Science B.V., Amsterdam., 2012)
This study aims to provide insights into the design and operation of full-scale post-combustion CO2 capture for a 500MWe sub-critical power plant through dynamic modelling and simulation. The development and validation of the dynamic models of the power plant and CO2 capture plant are described. In addition, the scale-up of the CO2 capture plant from pilot plant scale (where it was validated) to full scale is discussed. Subsequently the manner in which the two plant models were linked is discussed. A floating IP/LP crossover pressure configuration is used. A throttling valve is included between the LP turbine and draw-off point to prevent pressures at the crossover from dropping below required levels in the reboiler for solvent regeneration. The flue gas from the power plant is treated before it is sent to the CO2 capture plant. Four case studies are considered. The first investigates the effect of increasing solvent concentration on the performance of the power plant with the capture plant. The second investigates which absorber packing height offers a good balance between capital and operating costs. The two dynamic case studies show that the CO2 capture plant has a slower response than the power plant. They also reveal an interaction of CO2 capture level and power plant output control loops making it difficult to achieve steady power output levels quickly.